2016
DOI: 10.1016/j.atherosclerosis.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Lomitapide affects HDL composition and function

Abstract: Background: Lomitapide reduces low-density lipoprotein-cholesterol (LDL-C) but also high-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“… 299 However, the follow-up clinical studies determined that lomitapide not only reduced the level of LDL-C, but also resulted in a reduction in plasma HDL-C and ApoAI. 300 , 301 Owing to the combined benefits and risks, lomitapide is currently only available as an adjunctive orphan therapy to treat homozygous familial hypercholesterolemia.…”
Section: Atherosclerosis Therapiesmentioning
confidence: 99%
“… 299 However, the follow-up clinical studies determined that lomitapide not only reduced the level of LDL-C, but also resulted in a reduction in plasma HDL-C and ApoAI. 300 , 301 Owing to the combined benefits and risks, lomitapide is currently only available as an adjunctive orphan therapy to treat homozygous familial hypercholesterolemia.…”
Section: Atherosclerosis Therapiesmentioning
confidence: 99%
“…1 while baseline characteristics of patients are presented in Table 1 (Ref. [19,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]).…”
Section: Resultsmentioning
confidence: 99%
“…CVD complications, lomitapiderelated adverse events (AEs) were evaluated as safety outcomes (Table 4, Ref. [19,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]).…”
Section: Efficacy and Safety Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data from a phase III clinical study, lomitapide treatment was associated with a moderate decrease in HDL-C levels [45]. However, Yahya et al [50] showed that such a reduction in HDL-C was followed by the shift of the HDL subclass distribution toward more extensive, more buoyant HDL 2 particles, without significant impact on cholesterol efflux capacity (i.e., HDL functionality). Currently, no available data have demonstrated the effects of lomitapide on the sdLDL particles.…”
Section: Lomitapidementioning
confidence: 99%